Optical characterization of lower tropospheric aerosols by the Southern East Pacific Lidar station (Concepcion, Chile). (February 2016) - Montilla-Rosero, E.; Silva, A.; Jimenez, C.; Hernandez, R.; Saavedra, C.
Abstract: From February to September 2012 routine daily backscatter Lidar measurements were performed in Concepcion, a major city located in central Chile ( 36 ° 47 ′ S, 73 ° 7 ′ W, 12 amsl), providing the first regular measurements of tropospheric aerosol backscatter profiles in the country. The Lidar system, the first of its kind in Chile, has been developed locally to study the evolution of the atmospheric boundary layer (ABL) and vertical profiles of optical properties of lower and local tropospheric aerosols. This work presents the first results on aerosol optical properties retrieved for a Chilean coastal city, and it provides, for the first time, valuable long-term information about air pollution in the country, revealing seasonal variations of aerosol backscattering and extinction coefficients. In addition to determination of low content of tropospheric aerosols for this city, the elastic Lidar system was used to identify intrusions of external aerosol layers through significant increment of aerosol optical properties along the lower heights of local troposphere.